Flavonoids: Antioxidant Powerhouses and Their Role in Nanomedicine - Mehak Zahra; Heidi Abrahamse; Blassan P. George (MDPI AG, 2024)
This study emphasizes the critical role of antioxidants in protecting human health by counteracting the detrimental effects of oxidative stress induced by free radicals. Antioxidants-found in various forms such as vitamins, minerals, and the phytochemicals abundant in fruits and vegetables-neutralize free radicals by stabilizing them through electron donation. Specifically, flavonoid compounds are highlighted as robust defenders, addressing oxidative stress and inflammation to avert chronic illnesses like cancer, cardiovascular diseases, and neurodegenerative diseases. This research explores the bioactive potential of flavonoids, shedding light on their role not only in safeguarding health, but also in managing conditions such as diabetes, cancer, cardiovascular diseases, and neurodegenerative diseases. This review highlights the novel integration of South African-origin flavonoids with nanotechnology, presenting a cutting-edge strategy to improve drug delivery and therapeutic outcomes. This interdisciplinary approach, blending traditional wisdom with contemporary techniques, propels the exploration of flavonoid-mediated nanoparticles toward groundbreaking pharmaceutical applications, promising revolutionary advancements in healthcare. This collaborative synergy between traditional knowledge and modern science not only contributes to human health, but also underscores a significant step toward sustainable and impactful biomedical innovations, aligning with principles of environmental conservation.